(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study aims to examine the politeness strategies found in the novel The Summer I Turned Pretty by Jenny Han. In cross-linguistic pragmatics, politeness is a key element that functions as a system of interpersonal relations designed to minimize communication problems. For adolescents who are developing an awareness of social relationships and emotional regulation, politeness strategies are crucial for managing conversations in order to maintain connections and avoid misunderstandings. The objective of this study is to identify which strategies and the most frequently used strategies are employed by the teenage characters in this novel, namely Belly, Steven, Jeremiah, and Conrad. The theory employed is the politeness strategies framework by Brown & Levinson (1987), which comprises four strategies: bald on record, positive politeness, negative politeness, and off record. Using a qualitative descriptive method, 169 instances of politeness strategies spoken among the four characters were identified. Through the frequent use of positive politeness, the findings indicate that these characters tend to prioritize solidarity and closeness in their interactions. This study contributes to our understanding of how politeness strategies are represented in literary discourse, particularly among adolescent characters.